Identification of Potential Key Genes for Stem Polysaccharide Synthesis Based on Transcriptome Analysis of Different Developmental Stages of Dendrobium officinale - Tianwei Yang; Shiyu Huang; Shanshan Tian; Manrong Gao; Xiangjun Zhang; Longfei He; Shangwen Zhang (Horticulturae)
Dendrobium officinale holds significant value as a traditional medicinal plant, with its stems serving as the primary medicinal component and polysaccharides acting as the key active ingredients. To systematically analyze the biosynthetic pathways of polysaccharides and identify key genes involved in polysaccharide synthesis, this research assessed the water-soluble polysaccharide content and conducted transcriptome sequencing on stem tissues of D. officinale at different developmental stages. The findings revealed that the water-soluble polysaccharide level in D. officinale stems exhibited an increasing trend followed by a decrease, reaching its peak before flowering. Transcriptome analysis identified 5764, 6408, 4477, and 3809 differentially expressed genes (DEGs) in groups S1 vs. S2, S2 vs. S3, S3 vs. S4, and S4 vs. S5, respectively. The Kyoto Encyclopedia of Genes and Genomes Enrichment Analysis (KEGG) demonstrated that the DEGs in the S1 vs. S2, S2 vs. S3, and S3 vs. S4 groups were enriched in the starch and sucrose metabolism pathways. Based on the transcriptome sequencing results, expression heat maps of genes correlated with the polysaccharide synthesis pathways of D. officinale clearly showed changes in the expression of polysaccharide synthesis-related genes at five stages. Using weighted gene co-expression network analysis (WGCNA), three co-expression modules were identified, showing a significant positive correlation with fluctuations in the water-soluble polysaccharide content. From the light blue module with the highest correlation coefficient, 15 key genes potentially closely related to polysaccharide synthesis were identified. This study provides gene resources for the genetic improvement of D. officinale and detailed reference data for further elucidating the molecular mechanisms of polysaccharide biosynthesis.